Analisis Strategi Pemasaran Marketing Mix terhadap Keputusan Pembelian pada UMKM Kopi Estona - Adrian Willy Prata; Achmad Hasan Hafidzi; Ira Puspitadewi (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The development of industrial business in Indonesia is currently growing very rapidly. This can be seen from the many industries that are competing to win the hearts of consumers, through improving product quality and other things. The developments that have occurred have resulted in increasing competition. The business competition that has occurred has motivated business people to create strategies to make consumers satisfied with the products and services offered, because consumer behavior can change at any time for certain reasons. The aim of this research is to test and analyze the influence of product, price, promotion and location on purchasing decisions for Estona Coffee MSMEs. This type of research is causality research. The population in this research is consumers/customers of MSMEs of Estona Coffee. The sample used was 140 respondents using purposive sampling. The analysis tool uses multiple linear regression. The research results prove that product, price, promotion and location have a significant influence on purchasing decisions for Estona Coffee MSMEs. Keywords: Marketing Mix, Product, Price, Promotion, Location, Purchase Decision